2019
DOI: 10.1002/da.22884
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations of perceived unit cohesion with postdeployment mental health outcomes

Abstract: Background Prior investigations have found negative associations between military unit cohesion and posttraumatic stress disorder (PTSD); however, most relied on cross‐sectional data and few examined relationships of unit cohesion to other mental disorders. This study evaluates prospective associations of perceived unit cohesion with a range of mental health outcomes following combat deployment. Methods U.S. Army soldiers were surveyed approximately 1–2 months before deployment to Afghanistan (T0); and 1 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 41 publications
2
36
0
3
Order By: Relevance
“…These findings are consistent with previous research demonstrating the protective nature of unit cohesion, leader‐provided purpose, and leader‐provided meaning against depression symptoms and SI/DI in soldiers (Anderson et al, 2019; Sinclair et al, 2016; Trachik et al, 2020). In particular, the findings that unit cohesion concurrently predicted SI/DI and prospectively predicted changes in SI/DI post‐deployment are supported by previous research.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with previous research demonstrating the protective nature of unit cohesion, leader‐provided purpose, and leader‐provided meaning against depression symptoms and SI/DI in soldiers (Anderson et al, 2019; Sinclair et al, 2016; Trachik et al, 2020). In particular, the findings that unit cohesion concurrently predicted SI/DI and prospectively predicted changes in SI/DI post‐deployment are supported by previous research.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the findings that unit cohesion concurrently predicted SI/DI and prospectively predicted changes in SI/DI post‐deployment are supported by previous research. In military populations, unit cohesion has been shown to be protective against adverse mental health outcomes, such as depression, substance use, anxiety, and PTSD, and generally relates to higher levels of positive mental health indicators (Anderson et al, 2019; Bryan & Heron, 2015; Griffith, 2002, 2015; Oliver et al, 1999). This finding is also consistent with previous research demonstrating that unit cohesion can buffer against stressors (Mitchell et al, 2011), especially in a deployment environment when individuals are separated from other types of social support networks (Bierman & Kelty, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational support: The degree to which respondents received positive psychological support from their unit overall was assessed with the shortened Perceived Organizational Support measure, which has been widely used in military research [5556]; respondents indicated their level of agreement with the following items: 1) My unit strongly considers my goals and values; 2) My unit really cares about my well-being; 3) My unit cares about my opinion; and 4) My unit is willing to help me when I need a special favor (0 = strongly disagree to 5 = strongly agree ; α = .95).…”
Section: Introductionmentioning
confidence: 99%
“…Unit cohesion is the bond that unites service members to one another and the mission; 2 it has been prospectively associated with lower risk of adverse mental health outcomes like posttraumatic stress disorder (PTSD), depression, and substance use disorder (SUD). 2 While many have likened our collective experience of COVID-19 to wartime, we must consider what this crisis is like for those who have actually served and how we may best support them during the pandemic. We may also learn from their courage, resilience, and expressions of camaraderie.…”
mentioning
confidence: 99%